Enabling highly selective H2O2 Electrosynthesis on graphene-based electrode by P-doped carbon nitride quantum dots for self-antibiofouling dissolved oxygen sensor via 2-electron oxygen reduction reaction - Chen, Kung-Hsing; Rinawati, Mia; Aulia, Sofiannisa; Chang, Ling-Yu; Chiu, Yen-Shou; Chang, Chia-Yu; Chen, Kuan-Jung; Huang, Wei-Hsiang; Su, Wei-Nien; Yeh, Min-Hsin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
Accurate monitoring of dissolved oxygen (DO) is essential for assessing aquatic environments, yet electrochemical DO sensors often suffer from biofilm formation on the electrode surface, compromising their sensitivity and durability. To address this limitation, hydrogen peroxide (H2O2), generated via the 2e− pathway of oxygen reduction reaction (2e−-ORR), serves as a potent biofilm-degrading agent on the electrode surface. However, most electrocatalysts for electrochemical DO sensors predominantly favor the four-electron pathway of oxygen reduction reaction (4e−-ORR), making selective 2e− ORR challenging. To overcome this bottleneck, in this study, we introduce a phosphorus-doped carbon nitride quantum dots/graphene (P-CNQDs/Gr) based DO sensors, engineered to enhance the 2e−-ORR selectivity, to realize the function of self-antibiofouling. The incorporation of PN bonding in P-CNQDs strengthens O2 adsorption and then promotes OOH* intermediates formation, facilitating efficient H2O2 formation. The generated H2O2 effectively disrupts biofilm adhesion on the electrode surface, facilitating an effective DO monitoring in the neutral medium. Our results demonstrated that the P-CNQDs/Gr achieves an impressive 85% selectivity for H2O2 in a neutral medium. Moreover, long-term stability tests in real aquatic samples reveal that the P-CNQDs/Gr based DO sensor retained 80.7% of its current after 48 h of continuous operation, indicating its self-antibiofouling and excellent durability for long-term applications. [Display omitted] •An engineered phosphorus-doped carbon nitride quantum dots (P-CNQDs) were successfully developed.•Integrating P-CNQDs on graphene promotes the selective 2e− oxygen reduction reaction.•The P and N atoms electronegativity gap enhances the of *OOH intermediates formation.•The generated H2O2 effectively disrupts biofilm, and the P-CNQDs/Gr electrode exhibits excellent stability.